91. Asymmetry of vestibular myogenic evoked potentials in Parkinson disease. Issue 12 (December 2017) - Piscosquito, G.; Lullo, F.; Provitera, V.; Prisco, C.; Zamprotta, L.; Lanzillo, B.; Manganelli, F.; Santoro, L.; Nolano, M.
Abstract : Degeneration of several brainstem nuclei occurs in Parkinson disease (PD). Vestibular-evoked-myogenic-potentials (VEMPs) represent a valuable tool to assess the function of these structures. VEMPs abnormalities have been reported in PD. We used this tool to assess the asymmetry between the two sides and the difference between anterior and posterior muscles in patients with PD. VEMPs were recorded simultaneously and bilaterally from sternocleidomastoideus (SCM), splenius (SPL), trapezius (TRP) and orbicularis oculi (OO) muscles in 20 idiopathic PD patients (mean age 63.1 ± 9.4 years) with normal BAEPs. Stimulation was binaural and recordings were performed with flexed neck in clinostatic position. SCM VEMPs asymmetry (amplitude difference > 30%) was found in 11/20 patients (55%) and was concordant with the most clinically affected side in 9/11. All muscles showed a concordant side asymmetry. Potential amplitudes from posterior muscles were lower (SPL: 6.8 ± 12.7, TRP: 6.0 ± 11.6) than anterior ones (SCM: 26.9 ± 39.5). VEMPs were absent more frequently in posterior muscles (17/40 traces in both SPL and TRP; 3/40 in SCM). VEMPs alterations confirmed the involvement of vestibule-spinal system in PD. Side to side and anterior-posterior asymmetry of vestibulo-spinal reflex impairment could contribute to camptocormia, postural instability and gait imbalance in PD.